A Quick Sequential Organ Failure Assessment (qSOFA) Score Greater than 1 and Shortened Ampicillin Use Predict Death and One-Year Mortality in Hospitalized Patients with Non-Perinatal Invasive Listeriosis: A Retrospective Analysis of 118 Consecutive Cases - Shuh-Kuan Liau; Cheng-Chieh Hung; Chao-Yu Chen; Yi-Chun Liu; Yueh-An Lu; Yu-Jr Lin; Yung-Chang Chen; Ya-Chung Tian; Fan-Gang Tseng; Hsiang-Hao Hsu (Microorganisms)
Listeria monocytogenes causes listeriosis, a serious foodborne illness with a high mortality rate, especially in vulnerable populations. It accounts for 19% of foodborne deaths, with invasive cases having a mortality rate of up to 44%, leading to conditions like meningitis, bacteremia, and meningoencephalitis. However, the prognostic factors remain unclear. This study examines the hospital outcomes of invasive listeriosis and identifies risk factors for in-hospital and one-year mortality. We analyzed the electronic medical records of 118 hospitalized patients with non-perinatal, culture-proven invasive listeriosis collected over a 21-year period. The in-hospital mortality rate was 36.4%, with only 33.1% surviving one year and 22.0% surviving two years. The key findings indicate that a quick Sequential Organ Failure Assessment (qSOFA) score of ≥2 (OR 106.59, p < 0.001), respiratory failure (OR 7.58, p = 0.031), and shorter ampicillin duration (OR 0.53, p = 0.012) independently predicted poorer in-hospital outcomes. Additionally, a qSOFA score of ≥2 (OR 8.46, p < 0.001) and shorter ampicillin duration (OR 0.65, p < 0.001) were linked to higher one-year mortality. This study is the first to identify a qSOFA score of ≥2 as a significant marker for high-risk invasive listeriosis patients, with poorer outcomes linked to a qSOFA score of ≥2, respiratory failure, and shorter ampicillin use.